PENGARUH PENGEMBANGAN KARIR, STRES KERJA DAN PEMBERDAYAAN KARYAWAN TERHADAP TURNOVER INTENTION DI KAYUMANIS NUSA DUA PRIVATE VILLA & SPA BALI - Ni Kadek Sudnanti; Ni Wayan Wijayanti (Jurnal Ilmiah Manajemen & Bisnis, 2018)
The Influence of Career Development, Work Stress, and Employe Empowerment on Turnover Intention at Kayumanis Nusa Dua Private Villa & Spa Bali. This research is motivated by the problem of turnover intention which is increasing annually at Kayumanis Nusa Dua Private Villa & Spa. This study aims to determine the impact of career development, work stress, the influence of employee empowerment on turnover intention, also the influence of career development, work stress, and employee empowerment on turnover intention at Kayumanis Nusa Dua Private Villa & Spa. This research was conducted at Kayumanis Nusa Dua Private Villa & Spa, using Kayumanis Nusa Dua Private Villa & Spa employees as respondents. The number of respondents in this study were 80 people taken by saturated sample techniques. The types of data are quantitative data. Sources of data are primary data and secondary data. Data collection techniques used a questionnaire with closed questions as measured by the Likert scale. The data analysis technique used in this study is a multiple linear regression analysis technique which operated by the SPSS version 23.0 program. The results of indicate that career development has a negative effect on turnover intention, work stress has a positive effect on turnover intention, employee empowerment has a negative effect on turnover intention, and career development, work stress and employee empowerment significantly influence turnover intention on Kayumanis Nusa Dua Private Villa & Spa. Keywords: career development, work stress, employee empowerment, turnover intention